2022
DOI: 10.1093/cercor/bhac444
|View full text |Cite
|
Sign up to set email alerts
|

Development of neonatal brain functional centrality and alterations associated with preterm birth

Abstract: Formation of the functional connectome in early life underpins future learning and behavior. However, our understanding of how the functional organization of brain regions into interconnected hubs (centrality) matures in the early postnatal period is limited, especially in response to factors associated with adverse neurodevelopmental outcomes such as preterm birth. We characterized voxel-wise functional centrality (weighted degree) in 366 neonates from the Developing Human Connectome Project. We tested the hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Resting-state functional MRI (rs-fMRI) data were pre-processed as in our previous work; [55] for more details see Supplemental Information. Functional connectivity was evaluated using a measure of weighted degree centrality at the voxel-level (i.e., the sum of the correlations between the time-series of each voxel and all other voxels within a gray matter mask of the brain) [31,56]. Edges with a correlation coefficient below a threshold of 0.2 were excluded and the degree centrality values for each voxel in the gray matter mask were z-scored and used in subsequent between-subgroup analyses.…”
Section: Exploring Neonatal Brain Differences Between Subgroupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resting-state functional MRI (rs-fMRI) data were pre-processed as in our previous work; [55] for more details see Supplemental Information. Functional connectivity was evaluated using a measure of weighted degree centrality at the voxel-level (i.e., the sum of the correlations between the time-series of each voxel and all other voxels within a gray matter mask of the brain) [31,56]. Edges with a correlation coefficient below a threshold of 0.2 were excluded and the degree centrality values for each voxel in the gray matter mask were z-scored and used in subsequent between-subgroup analyses.…”
Section: Exploring Neonatal Brain Differences Between Subgroupsmentioning
confidence: 99%
“…Edges with a correlation coefficient below a threshold of 0.2 were excluded and the degree centrality values for each voxel in the gray matter mask were z-scored and used in subsequent between-subgroup analyses. Whilst other functional network measures are available (i.e., participation coefficient and within module-z [57], we opted to study degree centrality as we recently showed this to be disrupted in preterm born neonates [31]. Furthermore, degree centrality is a good voxel-wise summary measure of connectivity strength, which is reliable and correlates with relevant phenotypes, such as age and sex [58].…”
Section: Exploring Neonatal Brain Differences Between Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each participant, rsFC matrices were calculated using Pearson’s correlations between pairs of all 374 regional time series. A threshold of 0.2 was used to eliminate weak correlations (i.e., weights of edges with r 2 0.2 were retained) and a Fisher Z-transformation was applied (Buckner et al, 2009; Fenn-Moltu et al, 2022; Zalesky et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, the functional correlates of such anatomical alterations are still poorly understood despite the common impairments observed at the behavioral level in children born preterm. In the past decade, functional MRI (fMRI) has allowed identifying precursors of spatially organized functional brain networks in the resting-state activity of preterms, which show reduced maturation in terms of long-range connectivity compared to full-terms (Doria et al, 2010) and alterations of network-level properties (Fenn-Moltu et al, 2023) that persist until TEA (Gozdas et al, 2018) and childhood (Wehrle et al, 2018). Yet, understanding how these alterations affect the efficiency of brain networks for processing environmental information requires investigating the dynamic aspects of the brain activity that go beyond the temporal resolution of the Blood Oxygenation Level Dependent (BOLD) effect captured by fMRI.…”
Section: Introductionmentioning
confidence: 99%